Persistent Hypoglycemia in Venlafaxine Overdose - Ling, Ying; Khara, Lovedeep; Alvarez, George; McBeth, Paul B (Archives of Clinical and Medical Case Reports, 2019)
Venlafaxine is a serotonin norepinephrine reuptake inhibitor thought to have little effect on glucose metabolism. However, hypoglycemia in venlafaxine overdose has been described in a paucity of case reports, and we present a unique case of venlafaxine induced hypoglycemia complicated by malnutrition and concomitant alcohol intoxication. A 29-year-old male presented to the emergency department after a venlafaxine XR overdose and concomitant alcohol intoxication. He was admitted to the ICU with serotonin syndrome, found to be hypoglycemic, and started on intravenous dextrose. Despite clinical improvement over a few days, and being reinitiated on an oral diet, the patient’s glucose remained low. 65 hours after ingestion of the venlafaxine, subcutaneous octreotide was administered and the hypoglycemia resolved. We suggest early and repeated measurements of blood glucose in patients presenting to the emergency department and ICU with overdose ingestions, and to maintain a multifactorial approach to the etiology of any resultant hypoglycemia.